Chapter La Città dei Mestieri. Educazione al patrimonio e comunità di pratica - MULINACCI, LAERTE (Studies on Adult Learning and Education, 2022)
History and its teaching have progressively lost authority while, at the same time, the question of history remains evident: it is an essential human instinct to question oneself about one's past that manifests itself even without realizing it (just think of the family sphere). The consumption of history, despite the 'epistemological crisis' that characterized it, is on the rise: the success of festivals, historical novels, fiction and video games inspired by events from our past testify it.